Ancestral Stem Cell Reprogramming Genes Active in Hemichordate Regeneration - Humphreys, Tom; Weiser, Keith; Arimoto, Asuka; Sasaki, Akane; Uenishi, Gene; Fujimoto, Brent; Kawashima, Takeshi; Taparra, Kekoa; Molnar, Janos; Satoh, Noriyuki; Marikawa, Yusuke; Tagawa, Kuni (Frontiers in Ecology and Evolution, 2022)
Hemichordate enteropneust worms regenerate extensively, in a manner that easily recalls the amazing regeneration for which planaria and hydra are famous. Although hemichordates are often placed as the most ancestral extant phylogenetic group at the base of the deuterostome evolutionary line leading to chordates, mammals and humans, extensive regeneration is not known in any of these more advanced groups in the lineage. Here we show that hemichordates might deploy functional orthologues of the canonical Yamanaka stem cell reprogramming factors, Oct4, Sox2, Nanog and Klf4, as they regenerate. These reprogramming factors are not expressed during the meager limb, fin, eye and other regeneration that represent the best examples of regeneration in chordates. Evolutionarily, the chordates may have lost the ability to mobilize the reprogramming factors in response to damage or hemichordates may have co-opted the factors for their extensive regeneration. The robustness of these pluripotency gene circuits in the inner cell mass and in formation of iPSC from mammalian somatic cells shows the programs are intact in mammals and humans and these circuits may respond to the yet unknown gene regulatory signals mobilizing full regeneration in hemichordates.